ANALISIS TERHADAP PERMOHONAN PENERBITAN AKTA KELAHIRAN YANG DITOLAK OLEH DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL PASCA-PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XI/2013 - Ria Evarini Natalia; Ahmad Redi (Fakultas Hukum Universitas Tarumanagara, 2020)
The state of Indonesia, which is a constitutional state, has the right to obtain the identity of Indonesian citizens. One of them is getting a birth certificate. Historically, the establishment of the Indonesian state had the goal of creating a country that was prosperous, orderly, safe, and far from poverty. The goal of the Indonesian state, which wants its people to prosper, includes obligations that must be fulfilled. With the obligation to improve the welfare of the people, it is not spared from service so that a state law order is formed. The government that regulates state administration is the Population and Civil Registration Service. In the decision which states that the Petitioner who is 66 (sixty six) years old wants to process a petition that has been born that was rejected by the Population and Civil Registration Service then the applicant who goes to the District Court which should be in accordance with the decision of the constitutional court which is no longer under the authority of the court country to issue birth certificates. So that population action and civil registration are not in accordance with the objectives of the Indonesian state, namely to create a prosperous Indonesian state by carrying out population administration services.